“Umah Macuy” Sebagai Center Of Learning Masyarakat Tertinggal Desa Napallicin Kecamatan Ulu Rawas Kabupaten Musi Rawas Utara - Gusti Aldo Wijaya; Euis Nur Af’idah; Wulan Utami Triyani; Ines Sr; Femi Wulandari; Desti Sia Mita; Kokoh Padli; Rinaldi Akbar; Ari Nopriansyah; Ahmad Riki; Mauliza Risma; Awang Wahyu Sadewa; Ngatijah; Yogi Rosa Putra; Nindia Saputri (CV. Multi Kreasi Media, 2023)
Napallicin Village is one of the underdeveloped villages located at the end of North Musi Rawas Regency with access only by one land access route, Tanah Merah, which takes ±4-5 hours. In addition to difficult access, the community's economy is still below the minimum wage and there is also no internet network that functions to upgrade knowledge. Based on the results of observations and interviews with the village head and the people of Napallicin Village, it is known that education in this village is categorized as low because 85% of the community, especially teenagers and the elderly, are illiterate because they do not go to school and the highest is only elementary school graduates. The low level of parental education, of course, affects the motivation to go to a further level. This problem is exacerbated by the fact that the educators who teach in schools are not in accordance with their competence and also the number is still very minimal. This certainly has an impact on the lack of literacy skills of children, adolescents and the elderly. Therefore, one of the solutions offered is